Overweight, obesity and arterial hypertension in young and middle-aged military servants - I. M. Davidovich; O. V. Afonaskov; A. V. Kozyrenko (Кардиоваскулярная терапия и профилактика)
Aim. То study the prevalence of normal weight, overweight (OW) and obesity (O) in patients with arterial hypertension (AH) — contract military servants. To assess the impact of body weight variants into AH pathogenesis, risk factors (RFs) and associated clinical conditions (ACC) in this group of patients.Material and methods. In 349 AH patients, young and middle-aged males working as contract military servants (mean age 40,2±0,32 years), height (m) and weight (kg) were measured, with body mass index (BMI) calculation. Total cholesterol (TCH) level retinopathy and left ventricular hypertrophy (LVH) by Sokolov-Lyon index were also assessed. The control group included 665 contract military servants without AH.Results. In the main group of AH patients, OW and О were registered in 82,8%, significantly more often than in the controls. О was associated with significantly higher levels of systolic and diastolic blood pressure and TCH, comparing to those levels in AH patients with normal body weight.Conclusion. Among young and middle-aged men with AH and O, the majority of the patients were at high cardiovascular risk.